Development of a Point-of-Use Drinking Water Purifier Using Aluminum Oxide-Based Flocculent-Disinfectant Composite - Patricia Nemate; Feleke Zewge; Eyobel Mulugeta (Universitas Gadjah Mada, 2023)
One in every three people in the world still lacks access to clean drinking water. Aside from microbiological pollution, high fluoride content in drinking water is one of the most serious problems in African countries. This study aimed to contribute to the availability of clean water by developing a point-of-use drinking water purifier using an aluminum oxide-based flocculent-disinfectant composite. Batch experiments were conducted to determine factors affecting fluoride removal efficiency (FRE) and E. coli log reduction efficiency. AO of 75 mg/L, 800 mg/L alum, lime (35% alum dose), and 1.5 mg/L Ca(OCl)₂ doses achieved 95% FRE and 5 log10 reductions of E. coli using 15 mg/L as initial fluoride concentration ([F−]0), and 105 CFU/100 mL E. coli concentration. [F−]0 affected FRE but showed no effect on E. coli log reduction. The optimum pH of the solution for both FRE and E. coli log reduction was found to be in the range of 4–8. Three prototypes in powder form were developed. The prototypes were tested on real water samples from the Ethiopian Rift Valley, and the results were found to be within the drinking water standards, thus indicating the capability of the developed products to purify contaminated water for human consumption.